Proximal Policy Optimization for Crowd Evacuation in Complex Environments—A Metaverse Approach at Krung Thep Aphiwat Central Terminal, Thailand - Sushank Chaudhary; Nitinun Sinpan; Pruk Sasithong; Sunita Khichar; Panithan la-Aiddee; Natt Leelawat; Amir Parnianifard; Suvit Poomrittigul; Lunchakorn Wuttisittikulkij (IEEE Access)
Efficient crowd evacuation from railway platforms is critical for passenger safety during emergencies. This study introduces a novel dynamic emergency evacuation route generator using the Proximal Policy Optimization (PPO) algorithm within a custom-built 3D simulation environment developed in Unity. We independently created a detailed digital twin of Krung Thep Aphiwat Central Terminal, Thailand’s largest train station, and implemented all elements of the simulation, including the Social Force Model, to accurately replicate crowd behaviors and interactions during evacuation scenarios. Through extensive training over 3,000,000 episodes, our PPO-based model achieved significant improvements in evacuation efficiency. The results indicate that in a major emergency scenario, increasing the number of agents in the station reduced the number of remaining passengers from 111 to just 6, highlighting the model’s effectiveness. Similarly, in a minor emergency scenario, the average number of remaining passengers dropped from 38 to 1 with the addition of more agents. These findings confirm the model’s ability to adapt to different emergency conditions, offering a practical and scalable solution for enhancing evacuation strategies in high-density environments. Furthermore, increasing the agents’ sight range also improved evacuation efficiency, with a 20-meter sight range yielding the best results.